Implikasi Era Society 5.0 Dalam Menguatkan Sikap Moderasi Beragama Bagi Siswa Sekolah Dasar - Mochammad Rizal Ramadhan (IAI Al Khoziny Buduran Sidoarjo, 2021)
The purpose of this study is to discuss how to strengthen the attitude of religious moderation for elementary school students in the era of society 5.0. Moderation needs to be strengthened from an early age because through this, students can face the challenges that will be faced in the era of society 5.0 that is right in front of their eyes. Many studies have discussed about moderation but have not found the right way to strengthen it, through this paper will explain several alternative ways so that moderation can be strengthened. Even though the era of society 5.0 has come with an all-digital era, with the readiness of individuals to the community, moderatism will not fade because it has been strengthened in a pluralistic society.